Diary Of A Wimpy Kid : The Last Straw - Kinney, Jeff; Author (ill) (Puffin London, 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school.
Keywords: Children's Literature - Fiction : Humorous